Trump's assault on international law: Its impact on the WTO - Arredondo, Ricardo (2020)
The assumption of power of the President of the United States Donald J. Trump meant a turn radical both internally and internationally, which contributed to exacerbating divisions in American domestic politics, while bringing with it important consequences negatives for multilateralism and existing international legal regimes. This attack, manifested in different areas of international law, has among its objectives variousinternational organizations, whose most recent example has been the suspension of funds to the World Health Organization (WHO) amid the coronavirus pandemic. The World Trade Organization has not only not escaped this onslaught but has been one of whites particularly chosen by the US administration. This work analyzes Trump's attack on the WTO, its consequences, and possible solutions to this impasse.